(untitled) (Altre Modernità, 2022)
In the context of a growing tendency towards teaching practices based on digital innovation, which the Covid-19 outbreak has further accelerated, experimenting with cooperative writing/translation projects based on Wiki technology has started to attract the attention of university scholars. A number of projects have thus emerged that exploit the Wikimedia ecosystem as a multilingual working environment for online authentic tasks, which are particularly appropriate for a new generation of “digital natives” who have been facing (forced) distant learning activities. Indeed, experience shows that the very myth of the digital natives’ fluency in the use of ICT is to be questioned, and the need for the development of ICT literacy and related transversal competences is strongly advocated. Against this background, the article reports on a project completed with distance learning-based activities at the University of Bari: “Transl/Editathon@Uniba. A Wikivoyage To Puglia”. The project had a twofold aim: it channelled resources with different expertise and knowledge backgrounds to offer a multi-disciplinary approach to tourism discourse, translation skills and IT competence; it aimed at raising awareness in students that a cooperation-based approach in a digital environment can enhance their transversal skills. The students’ ability in narrating their territory via Wikivoyage, and their feeling part of a virtual community, was the project’s added value in a time when distance(s) in geographical and interpersonal terms seem to have been loosening any sense of belonging.